Low-Frequency Repetitive Transcranial Magnetic Stimulation in the Early Subacute Phase of Stroke Enhances Angiogenic Mechanisms in Rats - Yookyung Lee; Byung-Mo Oh; Sung-Hye Park; Tai Ryoon Han (Annals of Rehabilitation Medicine, 2022)
Objective To characterize the repetitive transcranial magnetic stimulation (rTMS) induced changes in angiogenic mechanisms across different brain regions. Methods Seventy-nine adult male Sprague-Dawley rats were subjected to a middle cerebral artery occlusion (day 0) and then treated with 1-Hz, 20-Hz, or sham stimulation of their lesioned hemispheres for 2 weeks. The stimulation intensity was set to 100% of the motor threshold. The neurological function was assessed on days 3, 10, and 17. The infarct volume and angiogenesis were measured by histology, immunohistochemistry, Western blot, and real-time polymerase chain reaction (PCR) assays. Brain tissue was harvested from the ischemic core (IC), ischemic border zone (BZ), and contralateral homologous cortex (CH). Results Optical density of angiopoietin1 and synaptophysin in the IC was significantly greater in the low-frequency group than in the sham group (p=0.03 and p=0.03, respectively). The 1-Hz rTMS significantly increased the level of Akt phosphorylation in the BZ (p<0.05 vs. 20 Hz). Endothelial nitric oxide synthase phosphorylation was increased in the IC (p<0.05 vs. 20 Hz), BZ (p<0.05 vs. 20 Hz), and CH (p<0.05 vs. 20 Hz and p<0.05 vs. sham). Real-time PCR demonstrated that low-frequency stimulation significantly increased the transcriptional activity of the TIE2 gene in the IC (p<0.05). Conclusion Low-frequency rTMS of the ipsilesional hemisphere in the early subacute phase of stroke promotes the expression of angiogenic factors and related genes in the brain, particularly in the injured area.